All the People: Uncovering the Hidden History of Cooperation, Cooperative Movements, and Communalism in America - Patmore, Greg (Labour / Le Travail, 2013)
The article reviews the book, "For All the People: Uncovering the Hidden History of Cooperation, Cooperative Movements, and Communalism in America," by John Curl.
Keywords: COOPERATION – History; CURL; John; FOR All the People: Uncovering the Hidden History of Cooperation; Cooperative Movements & Communalism in America (Book); Nonfiction